The Impact of Rapid Urban Growth on Potential Groundwater Pollution in Ngemplak Sub-District, Sleman District - Rivi Neritarani; Sadewa Purba Sejati (Department of Urban and Regional Planning, Diponegoro University, 2021)
Ngemplak Sub-District is one of the administrative regions in Sleman Regency which has experienced quite intensive urban development. Based on several studies, this region experienced a fairly rapid change in landuse. This landuse changes has resulted in pressure on the natural resources in this region, especially water resources. The study aims to develop a strategy to maintain the sustainable function of land resources in the midst of massive land changes in Ngemplak Sub-District. This research uses landuse comparative method at two different times to identify rapid urban growth. Whereas to identify potential groundwater pollution, this research uses the GOD method which is use three parameters, they are groundwater occurrence (G), overall aquifer class (O), and depth to water table (D). Based on the results of data processing, there was an increase in built-up area in Ngemplak Sub-District from 2006 to 2015 amounting to 235. 58 hectares. This increase in built-up area is a trigger factor for the emergence of environmental problems, namely the exploitation of water resources found in this region. Based on the results of data processing using the GOD method, the overall potential groundwater pollution in the Ngemplak Sub-District is included in the extreme class.